Dimensional Stability and Moisture Content of White Teak Wood Treated with Nano-SiO2 and Furfuryl Alcohol - Aswad, Nini H.; Ahmad, Siti Nurjanah; Putri, Tryantini S.; Nayono, Satoto Endar; Tachrir, .; Tumpu, Miswar (Engineering, Technology & Applied Science Research, 2025)
The objective of this study is to assess the impact of nanoparticle impregnation on the moisture content and dimensional stability of white teak wood derived from Southeast Sulawesi, Indonesia. The impregnation method was employed to process white teak wood samples, with varying concentrations of Furfuryl Alcohol (FA) and nano-SiO2. The wood samples underwent examinations to quantify the moisture content, dimensional changes, and mechanical properties after treatment, including Weight Percent Gain (WPG), Bulking Effect (BE), Anti-Swelling Efficiency (ASE), and Water Uptake (WU). The results indicated that the dimensional stability of white teak wood was considerably enhanced with the impregnation process, as evidenced by a decrease in swelling, compared to the untreated wood. Additionally, the moisture content of impregnated wood decreased significantly, suggesting improved moisture resistance. These findings demonstrate that the application of nano-SiO2 and FA as impregnation materials offers a viable solution for enhancing the quality and durability of white teak, potentially expanding its applications in the construction sector.